PERUBAHAN MORFOLOGI STRUKTUR MIKRO PADUAN Cu-Zn 70/30 YANG DILAKUKAN TMCP DI SUHU 300°C DENGAN VARIASI WAKTU TAHAN PEMANASAN - Eka Febriyanti; Ahmad Fadli; Amin Suhadi; Rini Riastuti (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2018)
Cu-Zn alloy (70/30) used extensively for core and tank automotive radiator, ammunition component, and architectural hardware so that susceptible to exposure of corrosive environments such as seawater and ammonia environments. Therefore, this research focuses on the study of mechanical properties and corrosion resistance Cu-Zn 70/30 by implementing warm rolling TMCP method. Thermo-Mechanical Controlled Processing (TMCP) is one method consists of controlled heating and controlled forming to produce high quality materials. Rolling process was conducted in reversible way with deformation degree of 60% (30%-30%) and before each pass of the rolling the material is heated up to temperature 300oC with different holding time from 30, 60, and 120 minutes. The results showed that as the longer holding time of the heating and was continued by further deformation, it affects the grain size to be much smaller from 92.2 μm to 36.5 μm. In addition, it is also found an increasing of annealed twin, deformed twin, as well as finer and newer grains that indicate partial dynamic recrystallization.